Model Keraguan Mengambil Keputusan Karir Pada Mahasiswa Tahun Pertama - Dian Ratna Sawitri (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2008)
The present study examines the theoretical model on how Identity status and self-efficacy in decision making process has indirect influences on the level of the indecisiveness for choosing future career in college students during their freshman year.With a sample of 389 respondents of Public University students at Semarang in their freshman year, we analyze the structural equation model using AMOS program version 16.0., which then indicates that the Theoretical Model can explain on how the indecisiveness in choosing future career. Identity status has indirect influence to the level of indecisiveness when the self efficacy for choosing future career is simultaneously measured, The study also explains that the higher the respondents have in self efficacy, the more decisive they are in choosing their future career. Moreover, the results In details shows that achieved Identity status leads to the high level of selfefficacy and diffused Identity status directly influences the lower level of self efficacy in choosing future career whereas the remaining identity status which are moratorium and foreclosure Identity status, both have no Influence on self efficacy for choosing future career.